HSLA Steels 2015, Microalloying 2015 & Offshore Engineering Steels 2015 Conference Proceedings - The Chinese Society for Metals; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This is a collection of papers presented at the joint conference of the 7th International Conference on High Strength Low Alloy Steels (HSLA Steels 2015), the International Conference on Microalloying 2015 (Microalloying 2015), and the International Conference on Offshore Engineering Steels 2015 (OES 2015). The papers focus on the exchange of the latest scientific and technological progresses on HSLA steels, microalloying steels, and offshore engineering steels over the past decades. The contributions are intended to strengthen cooperation between universities and research institutes, and iron and steel companies and users, and promote the further development in the fields all over the world.
Keywords: Metals; Materials -- Analysis; Materials; Metals and Alloys; Characterization and Analytical Technique; Materials Engineering